THE TEACHER’S STRATEGY IN TEACHING NARRATIVE WRITING USING THINK PAIR SHARE AT SECOND YEAR OF MTsN MOJOROTO ACADEMIC YEAR 2012/2013 - Fujiyanti, Rofikoh (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aim of this study was getting the information deeply about The Teacher’s Strategy in Teaching Narrative Writing at Second Year of MTsN Mojoroto Kediri. This research used descriptive qualitative design. Observation, Interview, Questioner  and documentation were used in collecting the data. The second year of MTsN Mojoroto is taken as the focus of research. The result shows that (1) The Teacher’s Strategy  in Teaching Narrative Writing Using Think Pair Share at Second Year of MTsN Mojoroto Procedure using Think Pair and Share is good. (2) The Reasons in Teaching Narrative Writing Using Think Pair Share at Second Year of MTsN Mojoroto. Teaching narrative writing more success and effective. (3) The Result in Teaching Narrative Writing Using Think Pair Share at Second Year of MTsN Mojoroto, it is shown that students’ achievement is good score. In the F-class has average  6.25% remedial, that are three students get score less 75. In the G-class has average is 79.21 and 8.51% remedial, that are four students get score less 75. And then, in the H-class has average is 78 and 14.58% remedial, that are seven students get score less 75. The students will remedial if get score less 75. (4) The Problems in Teaching Narrative Writing Using Think Pair Share at Second Year of MTsN Mojoroto using Think Pair Share need many time, some time there are the students are not get partner, too many in group. (5) The students’ Responds in Teaching Narrative Writing at second year of MTsN Mojoroto. From 128 students there are 117 feel happy and eleven of the students feel unhappy.